2021
DOI: 10.3889/oamjms.2021.6097
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Estimated Glomerular Filtration Rate and Parathyroid Hormone Levels in Predialysis-chronic Kidney Disease Adult Patients at Sanglah General Hospital, Bali, Indonesia

Abstract: BACKGROUND: Chronic kidney disease (CKD) is a structural or functional kidney disease for more than 3 months. In predialysis CKD patients, the serum parathyroid hormone levels increase progressively since the early stages of the disease to maintain phosphate homeostasis. Glomerular filtration rate (GFR) has been widely accepted to assess renal function. The GFR assessment is used to determine the CKD stadium. AIM: This study aims to analyze the correlation between GFR and parathyroid hormone levels in predia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Previous studies reported that compared to normal albumin levels, patients with hypoalbuminemia had a lower 5-year survival rate (normal, 78% vs. hypoalbuminemia, 60%) and had lower 5-year recurrence-free rate or 5-years relapse-free survival than normal albumin level (normal, 78.9% vs. hypoalbuminemia, 73.5%). [17][18][19] This study also found a statistically significant association between CRP levels and NAC response. Elevated CRP is a secondary response to tumor necrosis, local tissue damage, and inflammation in malignancy patients.…”
Section: Original Articlesupporting
confidence: 74%
“…Previous studies reported that compared to normal albumin levels, patients with hypoalbuminemia had a lower 5-year survival rate (normal, 78% vs. hypoalbuminemia, 60%) and had lower 5-year recurrence-free rate or 5-years relapse-free survival than normal albumin level (normal, 78.9% vs. hypoalbuminemia, 73.5%). [17][18][19] This study also found a statistically significant association between CRP levels and NAC response. Elevated CRP is a secondary response to tumor necrosis, local tissue damage, and inflammation in malignancy patients.…”
Section: Original Articlesupporting
confidence: 74%
“…Albumin is the main determinant of oncotic plasma pressure as well as antioxidant, immunomodulatory, and detoxification functions. 6 Hypoalbuminemia in the perioperative period may affect organ vascularization, hamper the distribution of antibiotics, perpetuate inflammation, and induce intravascular coagulation. 7 Albumin level has long been used as a nutritional parameter and a risk factor for in-hospital and postoperative morbidity and mortality.…”
Section: Original Articlementioning
confidence: 99%